RampApp: herramienta digital para la cultura DIY en el deporte urbano - Borboa Félix, Jazmín Sugey (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
This thesis raises the need to provide the urban sports community with an accessible tool to promote the DIY culture (do it yourself) that allows designing and creating furniture for the practice of urban sports, such as custom ramps. This contribution from the design perspective is important for the community because it promotes accessibility, autonomy, personalization, adaptability, participation, and empowerment, which enriches the experience of athletes and strengthens their bond with sport. According to Iain Borden (2019) “DIY projects can also create new meanings and add social value”, referring to the granting of a new vision of the different spaces that are appropriated by different communities. The study begins with an investigation of the needs and preferences of the urban sports community in relation to the DIY culture, gathering information through surveys and interviews with skaters, rollers, and other athletes of different levels of experience and analyzing the current limitations in access to infrastructure and street furniture. With the results of the research, an easy-to-use interface for the mobile application is designed, developing functionalities that allow users to customize ramps or different furniture according to their preferences and needs. It is important to mention that the main objective of the application is to promote the initiative at the individual and community level, therefore, the creation of furniture is only a means to strengthen ties, not only with the community and the urban environment, but also in the self-knowledge, discovering personal skills in the design and management of small-scale projects for the appropriation of urban spaces.

Esta tesis plantea la necesidad de proporcionar a la comunidad del deporte urbano una herramienta accesible para promover la cultura DIY (hazlo tú mismo) que permita diseñar y crear mobiliario para la práctica del deporte urbano, como lo son las rampas personalizadas. Esta contribución desde la perspectiva del diseño es importante para la comunidad porque promueve la accesibilidad, la autonomía, la personalización, la adaptabilidad, la participación y el empoderamiento, lo que enriquece la experiencia de los deportistas y fortalecen su vínculo con el deporte. Según Iain Borden (2019) “los proyectos DIY también pueden crear nuevos significados y agregar valor social”, refiriéndose al otorgamiento de una nueva visión de los diferentes espacios que son apropiados por diferentes comunidades. El estudio comienza con una investigación de las necesidades y preferencias de la comunidad del deporte urbano en relación con la cultura DIY, recopilando información a través de encuestas y entrevistas a skaters, rollers y otros deportistas de diferentes niveles de experiencia y analizando las limitaciones actuales en el acceso a infraestructura y mobiliario urbano. Con los resultados de la investigación, se diseña una interfaz fácil de usar para la aplicación móvil, desarrollando funcionalidades que permitan a los usuarios personalizar rampas o diferente mobiliario de acuerdo con sus preferencias y necesidades. Es importante mencionar que el objetivo principal de la aplicación es promover la iniciativa a nivel individual y comunitario, por lo tanto, la creación de mobiliario es sólo un medio para fortalecer lazos, no sólo con la comunidad y el medio urbano, sino también en el autoconocimiento, descubriendo habilidades personales en el diseño y gestión de proyectos a pequeña escala para la apropiación de espacios urbanos.
Facultad de Arquitectura. Maestría en diseño avanzado
Keywords: info:eu-repo/classification/cti/4; FA-M-2024-0105; Tecnología móvil; Deporte urbano; Participación comunitaria; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18575